The growth response of sago palm (Metroxylon sagu Rottb.) explants in semi-solid and liquid media - Calio, Loradel Marbella S. (2010)
This study was conducted to determine the growth response of sago palm leaf explants in three different culture methods. The sago palm explants were cultured in semi-solid and liquid media (with and without support). These media were supplemented with two different pH values, 5.7 and 6.8. A total of six treatment combinations: (1) semi-solid media, pH 5.7, (2) semi-solid media, pH 6.8, (3) liquid media, pH 5.7, (4) liquid media, pH 6.8, (5) liquid media with filter paper bridge, pH 6.8 was used in this study. Four trials were performed in this study. Data collected were subjected to a two-way analysis of variance and nonparametric tests. Visual manifestations of growth of the explants were observed and were supported by the increase in the weights of the explants after four weeks. Results showed that the explants cultured in pH 5.7 responded similarly with those in pH 6.8. Furthermore, the explants cultured in liquid media (without support) exhibited better growth responses between the explants cultured using the filter paper bridge. However, the combined effects of pH and method used on the explants cultured using the filter paper bridge. However, the combined effects of pH and method used on the explants were the same. Thus, it can not be concluded as to what treatment combination the sago palm explants grows better. Contamination and tissue browning were the leading causes of the unequal number of replicates of different treatment combinations per trial. This may have impeded the accuracy of the conclusions of this study